Eleocharis neglecta (Cyperaceae), a new species from Konkan region of Maharashtra, India (Bangladesh Journal of Plant Taxonomy, 2016)
Eleocharis neglecta Borude, Chandore, Gholave & S.R. Yadav, a new species from Konkan region of Maharashtra, India is described and illustrated. This species belongs to Eleocharis subgen. Limnochloa (P. Beauv. ex Lestib.) Torr. and it is closely allied to Eleocharis dulcis (Burm. f.) Trin. ex Hensch. in having terete and septate culms.Bangladesh J. Plant Taxon. 23(2): 91-96, 2016 (December)